2020
DOI: 10.3390/cancers12010184
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin Intermediate Filaments as Potential Target for Cancer Treatment

Abstract: Intermediate filaments constitute the third component of the cellular skeleton. Unlike actin and microtubule cytoskeletons, the intermediate filaments are composed of a wide variety of structurally related proteins showing distinct expression patterns in tissues and cell types. Changes in the expression patterns of intermediate filaments are often associated with cancer progression; in particular with phenotypes leading to increased cellular migration and invasion. In this review we will describe the role of v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
158
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(161 citation statements)
references
References 134 publications
(191 reference statements)
1
158
0
2
Order By: Relevance
“…Table 1 summarizes some of the strategies and active principles employed to target vimentin, or reported to affect its function, some of which will be discussed below. In addition, several recent reviews have considered the role of vimentin as a drug target [10,166].…”
Section: Strategies To Modulate Vimentin Function: Focus On Extracellmentioning
confidence: 99%
“…Table 1 summarizes some of the strategies and active principles employed to target vimentin, or reported to affect its function, some of which will be discussed below. In addition, several recent reviews have considered the role of vimentin as a drug target [10,166].…”
Section: Strategies To Modulate Vimentin Function: Focus On Extracellmentioning
confidence: 99%
“…Our findings indicated that the levels of SMAD-2, SMAD-3, and their phosphorylated forms decreased in a dose-dependent way following APE treatment. Then, we analyzed vimentin, a type III intermediate filament and a major cytoskeletal component of motile mesenchymal cells, including metastatic tumor cells of epithelial origin 25 . Western blot analyses confirmed that MDA-MB-231 cells express high levels of vimentin which, after 48 h treatment with APE 300 μM EqC, became only slightly detectable suggesting APE-induced modifications of mesenchymal cell phenotype.…”
Section: Ape Decreased Mesenchymal and Increased Epithelial Markers Ementioning
confidence: 99%
“…Vimentin is overexpressed in most epithelial cancers and its levels correlate with tumor migration, invasion, and poor prognosis. Drugs inhibiting or reversing EMT also affect vimentin network organization 25 . Vimentin plays an important role in the formation of lamellipodia and filopodia 27 , specialized actin-rich plasma membrane protrusions with proteolytic activity, that allow cancer cells to degrade ECM with directional movement enabling cell invasion 28 .…”
Section: Ape Induced Met In Mda-mb-231 Cells By Modifying Vimentin Exmentioning
confidence: 99%
“…Among several pathways that induce EMT, a downregulation of epithelial protein, E-cadherin and a gain of the mesenchymal protein Vimentin have been found to play a critical role in cancer progression and metastasis [75,76]. Therefore, the tight regulation of these two functional opposite proteins is mandatory for cancer cells to control their aggressiveness and treatment responsiveness.…”
Section: Ubqlns and Emt Markersmentioning
confidence: 99%